Cell Type-Specific Human APP Transgene Expression by Hippocampal Interneurons in the Tg2576 Mouse Model of Alzheimer’s Disease - Höfling, Corinna; Shehabi, Emira; Kuhn, Peer-Hendrik; Lichtenthaler, Stefan F.; Hartlage-Rübsamen, Maike; Roßner, Steffen (Frontiers in Neuroscience, 2019)
Amyloid precursor protein (APP) transgenic animal models of Alzheimer’s disease have become versatile tools for basic and translational research. However, there is great heterogeneity of histological, biochemical and functional data between transgenic mouse lines, which might be due to different transgene expression patterns. Here, the expression of human APP by GABAergic hippocampal interneurons immunoreactive for the calcium binding proteins parvalbumin, calbindin, calretinin and for the peptide hormone somatostatin was analyzed in Tg2576 mice by double immunofluorescent microscopy. Overall, there was no GABAergic interneuron subpopulation that did not express the transgene. On the other hand, in no case all neurons of such a subpopulation expressed human APP. In dentate gyrus molecular layer and in stratum lacunosum moleculare less than 10% of human APP-positive interneurons co-express any of these interneuron markers, whereas in stratum oriens human APP-expressing neurons frequently co-express these interneuron markers to different proportions. We conclude that these neurons differentially contribute to deficits in young Tg2576 mice before the onset of Abeta plaque pathology. The detailed analysis of distinct brain region and neuron type-specific APP transgene expression patterns is indispensable to understand particular pathological features and mouse line-specific differences in neuronal and systemic functions.